Reforming primary and secondary education in Latin America and the Caribbean - de Moura Castro, Claudio...[et al.] (IDB WashingtonUS, 2000)
Focuses on how to improve primary and secondary education in Latin America and the Caribbean. Provides a set of objectives and strategies to guide the IDB in its support of primary and secondary education over the next decade.